2003
DOI: 10.1007/s00122-003-1381-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a radish introgression carrying the Ogura fertility restorer gene Rfo in rapeseed, using the Arabidopsis genome sequence and radish genetic mapping

Abstract: The radish Rfo gene restores male fertility in radish or rapeseed plants carrying Ogura cytoplasmic male-sterility. This system was first discovered in radish and was transferred to rapeseed for the production of F1 hybrid seeds. We aimed to identify the region of the Arabidopsis genome syntenic to the Rfo locus and to characterize the radish introgression in restored rapeseed. We used two methods: amplified consensus genetic markers (ACGMs) in restored rapeseed plants and construction of a precise genetic map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…Furthermore, analysis of reference (and nontransgenic) restored lines indicated that, in the B 1 line, ORF138 suppression was comparable to that in the D81 restored radish line . By contrast, ORF138 suppression by PPR-B in the B 2 line was similar to that seen in the SamRfo rapeseed line, which carries a large DNA introgression from radish comprising the entire Rfo locus ( Figure 2C) (Delourme et al, 1998;Giancola et al, 2003).…”
Section: Production Of Rapeseed Transgenic Plants Independently Exprementioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, analysis of reference (and nontransgenic) restored lines indicated that, in the B 1 line, ORF138 suppression was comparable to that in the D81 restored radish line . By contrast, ORF138 suppression by PPR-B in the B 2 line was similar to that seen in the SamRfo rapeseed line, which carries a large DNA introgression from radish comprising the entire Rfo locus ( Figure 2C) (Delourme et al, 1998;Giancola et al, 2003).…”
Section: Production Of Rapeseed Transgenic Plants Independently Exprementioning
confidence: 54%
“…All of the restored lines showed a drastic decrease in the ORF138 signal, but the level of inhibition appeared to vary between the different lines tested. The SamRfo rapeseed line, which contains a single copy of PPR-B on a large DNA region introgressed from radish (Delourme et al, 1998;Giancola et al, 2003), shows a nonhomogenous decrease in ORF138 synthesis in anther tissues. The sterility protein only (A) Analysis of total (Tot.…”
Section: The Removal Of Orf138 From the Tapetum Of Anthers Appears Tomentioning
confidence: 99%
“…Recent advances in canola genomics and molecular cytogenetics provide the possibilities to uncover the physical location of the Rfo locus in the canola genome. So far, a number of genetic maps have been constructed in canola and the molecular markers closely linked to the Rfo locus have been identified (Delourme et al 1994;Giancola et al 2003;Udall et al 2005;Hu et al 2008). The BAC clones linked to the Rfo locus have been identified from a large insert DNA library constructed from canola variety 'N1717', which carries the Rfo locus (Wu et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several papers have reported independently the cloning of the fertility restorer genes of Ogura and Kosena male sterility: Brown et al (2003), Desloire et al (2003), Giancola et al (2003), Koizuka et al (2003).…”
Section: Note Added In Proofsmentioning
confidence: 99%